2012
DOI: 10.1021/ma301906m
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Transitions of Poly(l-proline) in Copolypeptides with Poly(γ-benzyl-l-glutamate) Induced by Packing

Abstract: The hierarchical self-assembly and dynamics of poly(γ-benzyl-L-glutamate)-b-poly(L-proline) (PBLG-b-PLP) polypeptides are investigated with X-rays and solid state NMR. Both blocks possess helices stabilized solely either by hydrogen bonds (PBLG) or by steric hindrance (PLP) and are further packed in two different hexagonal cells. We report a trans/cis conformational change of PLP upon confinement that mimics the isomerization of isolated proline residues in proteins. These cis PLP conformations reside primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 23 publications
(42 reference statements)
3
45
0
1
Order By: Relevance
“…Polypeptides could be prepared with control over chain length, chain length distributions were narrow, and block copolypeptides were prepared. This method has been used by Iatrou and coworkers to prepare a number of different block copolypeptides, primarily PBLG segments connected to polymers of lysine, leucine, tryosine, as well as the imino acid proline, and their microphase separated morphologies have been studied in the bulk state [39,40].…”
Section: Insert Equation 11mentioning
confidence: 99%
See 1 more Smart Citation
“…Polypeptides could be prepared with control over chain length, chain length distributions were narrow, and block copolypeptides were prepared. This method has been used by Iatrou and coworkers to prepare a number of different block copolypeptides, primarily PBLG segments connected to polymers of lysine, leucine, tryosine, as well as the imino acid proline, and their microphase separated morphologies have been studied in the bulk state [39,40].…”
Section: Insert Equation 11mentioning
confidence: 99%
“…First, as oligoleucine composition was increased gel strength was found to increase dramatically. Furthermore, only hydrophobic segments with α-helical conformations were found to form strong gels, as evidenced by the inability of a K 160 (rac-L) 40 sample, where the racemic residues yield a disordered conformation, to form strong hydrogels. It was found that longer polyelectrolyte segments increase interchain repulsions such that the packing of the hydrophobic helices, which prefer formation of flat 2D sheets [81], must distort to minimize the overall energy of the system.…”
Section: Copolypeptide Hydrogelsmentioning
confidence: 99%
“…[9][10][11] Recently, hierarchical microstructures with multiple periods at different length scales have attracted great interests, which focus on the design of various hierarchical structures by tuning molecular topologies and chain compositions. [12][13][14][15][16][17][18][19][20][21][22][23][24] These structures are mainly prepared by the selfassembly of flexible copolymers. In contrast, the experimental studies on the hierarchical LC structures are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the experimental studies on the hierarchical LC structures are very limited. [20][21][22][23][24] The copolymers consisting of two kinds of rod blocks are one candidate for self-assembling into hierarchical LC structures. Iatrou et al synthesized poly(γ-benzyl-L-glutamate)-b-poly(L-proline) (PBLG-b-PLP) polypeptides in which both the PBLG and PLP adopt rigid helical conformations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation